Development of Interactive Learning Application CHEM-OWL (Substances and Their Changes) to Increase Students' Interest in Learning - M. Ilham Habiburrochman; Kriesna Kharisma Purwanto (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2025)
This research is motivated by issues related to the low interest in learning among seventh-grade students at SMPN 1 Sekaran, caused by several factors, including monotonous teaching methods and a lack of attention in developing more engaging learning media suitable for the students' conditions. This research aims to develop an interactive learning application called CHEM-OWL and test its validity through expert assessment and its effectiveness in increasing students' interest in learning. The method in this research is Research & Development (R&D), which uses the 4D development model limited to the development stage. The results of the media validation obtained an average percentage value of 95.30% with very valid criteria. The material validation obtained a percentage of 94.37% with very valid criteria. The N-gain value of students' learning interest before and after being treated with the media was 0.57, which falls under the moderate category. Thus, the interactive learning application CHEM-OWL is suitable for use and effective in increasing students' interest in learning in science education on the topic of matter and its changes. The implications of this research indicate that using Android-based learning applications such as CHEM-OWL can be an innovative solution for teachers to support more engaging and interactive learning for students.